Hemostasis and Thrombosis in Extreme Temperatures (Hypo- and Hyperthermia) - Levi, Marcel (Seminars in thrombosis and hemostasis, 2018)
The delicate biochemistry of coagulation and anticoagulation is greatly affected by deviations from the optimal temperature required for the interactions between various coagulation enzymes, cellular receptors, and intracellular mechanisms. Hyperthermia will lead to a prothrombotic state and, if sufficiently severe such as in heatstroke, a consumption coagulopathy, which will clinically manifest with the simultaneous appearance of intravascular thrombotic obstruction and an increased bleeding tendency. Hypothermia slows down the coagulation process, but as this seems to be adequately balanced by impairment of anticoagulant and fibrinolytic processes, its clinical effects are modest; however, hypothermia may be modestly linked to a somewhat higher risk of localized thrombosis. Restoration of a normal body temperature in patients affected by hyper- or hypothermia is the cornerstone for the management of associated coagulation derangements.